2015
DOI: 10.3390/s150204425
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Tang, C. Y. and Chen, X.Y. A Class of Coning Algorithms Based on a Half-Compressed Structure. Sensors 2014, 14, 14289–14301

Abstract: Due to an oversight by MDPI and the authors, the following numerical corrections were not made in the originally published article [1]. MDPI-Sensors and the authors would like to apologize for any inconvenience brought to the readers.[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Of the 3,059 genes regulated by maize ZmMYC2s, 814 are not JA responsive (Figure 5C), indicating that in addition to JA signaling, maize ZmMYC2s are also involved in other pathways. Whether and how maize ZmMYC2s participate in other signaling pathways remains unclear; however, studies in Arabidopsis have shown that MYC2 is also involved in ethylene and gibberellin signaling, by interacting with ETHYLENE INSENSITIVE 3 and DELLA, respectively (Hong et al, 2012;Song et al, 2014). This scenario is also supported by our comparison between the transcriptomes from W + OS-and MeJA-treated WT and myc2ab plants (Figures 3A, 5C), in that many fewer W + OSresponsive genes are regulated by ZmMYC2s than the ZmMYC2s-regulated JA-responsive genes.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 3,059 genes regulated by maize ZmMYC2s, 814 are not JA responsive (Figure 5C), indicating that in addition to JA signaling, maize ZmMYC2s are also involved in other pathways. Whether and how maize ZmMYC2s participate in other signaling pathways remains unclear; however, studies in Arabidopsis have shown that MYC2 is also involved in ethylene and gibberellin signaling, by interacting with ETHYLENE INSENSITIVE 3 and DELLA, respectively (Hong et al, 2012;Song et al, 2014). This scenario is also supported by our comparison between the transcriptomes from W + OS-and MeJA-treated WT and myc2ab plants (Figures 3A, 5C), in that many fewer W + OSresponsive genes are regulated by ZmMYC2s than the ZmMYC2s-regulated JA-responsive genes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the reported method and its further optimization , reactants were firstly weighed according to the mass ratio C:H 2 SO 4 (98 wt%):KMnO 4 :TiCl 4 of 1.0:4.8:0.28:0.23; the concentrated H 2 SO 4 was diluted to 77 wt% before reaction. Then, the quantified reactants were mixed in the order of diluted H 2 SO 4 , C, TiCl 4 , and KMnO 4 in beaker.…”
Section: Methodsmentioning
confidence: 99%
“…Then, select measurable parameters from the actual product and decide how to measure them. As for the measurement method, the coordinate measuring machine (CMM) and 3D scanner, which can extract the entire shape, are most commonly used, and other methods such as micrometer, vernier calipers, and microscopes are used to measure the dimensions of specific parts [14,15]. When the shape measurement is completed, it can be digitized into a 2D or 3D shape through a post-processing process, and using this, geometric design parameters must be extracted through the mathematical relationship of the gear tooth shape.…”
Section: Reverse Engineering Processmentioning
confidence: 99%